Kewenangan Pemerintah Desa Dalam Pengadaan Air Bersih Di Desa Lotas Kecamatan Rinhat Kabupaten Malaka - Usu, Benedikta; Yohanes, Saryono; Ratu Udju, Hernimus (Law Faculty, Nusa Cendana University, 2025)
Lotas Village, Rinhat District, Malaka Regency, often experiences problems in the management of natural resources, especially in the provision of clean water to the community. In relation to this, in Lotas Village, Rinhat District, Malaka Regency, problems often occur in the management of natural resources, especially in the provision of clean water to the community. This type of research is empirical legal research, namely research that focuses on studying problems in detail and in detail. In this study, the research location that the author took was Lotas Village, Rinhat District, Malaka Regency. Village Government Authority in Clean Water Procurement in Lotas Village, Rinhat District, Malaka Regency, which includes, Village Government Authority, Village Capacity and Resources, Inter-Institutional Cooperation, Environmental Aspects, Financing, and Infrastructure Management. Inhibiting Factors in Clean Water Procurement in Lotas Village, Rinhat District, Malaka Regency include, Limited Water Sources, Unsupportive Natural Conditions, High Costs for Distribution, Lack of Adequate Infrastructure, Dependence on Alternative Water Sources, Limited Village Budget, Policies and Regulations that are not yet Supportive.